Estudio de prefactibilidad para la instalación de una planta productora de ají Misqui-Uchu en salsa - Hayayumi Fong, Ricardo David (2016)
The following project is about the installation of a sauce production plant. This sauce is made from Misqui- Uchu chili, which is well known by connoisseurs for its taste and spiciness.